2021
DOI: 10.1002/jcu.22973
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of total anomalous pulmonary venous connection: 2D and 3D echocardiographic findings

Abstract: Total anomalous pulmonary venous connection (TAPVC) is a rare cyanotic congenital heart disease that accounts for less than 1% of all congenital heart diseases. TAPVC is characterized by the absence of pulmonary venous drainage into the left atrium. It is underdiagnosed in utero, with prenatal detection rates of less than 1.4%. The prenatal diagnosis of TAPVC affects the postnatal outcome, particularly in obstructive forms (critical TAPVC), since planned delivery and perinatal management are mandatory. Thus, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This in turn leads to reduced pulmonary venous return, LV filling and growth. In support of this flow-based mechanism reduced LV dimensions are similarly observed in fetuses with anomalous pulmonary venous drainage (23). This mechanism would in theory have greatest impact later in gestation when, in the normal fetus, increases in fetal pulmonary blood flow and LV size are usually observed.…”
Section: Neonatal Dimensions Outcomementioning
confidence: 80%
“…This in turn leads to reduced pulmonary venous return, LV filling and growth. In support of this flow-based mechanism reduced LV dimensions are similarly observed in fetuses with anomalous pulmonary venous drainage (23). This mechanism would in theory have greatest impact later in gestation when, in the normal fetus, increases in fetal pulmonary blood flow and LV size are usually observed.…”
Section: Neonatal Dimensions Outcomementioning
confidence: 80%
“…TAPVC is a critical CHD accounting for <1% of all CHDs ( 7 ). TAPVC is characterized by the absence of direct connection between the pulmonary venous and the LA.…”
Section: Discussionmentioning
confidence: 99%
“…The main supportive findings in the diagnosis of TAPVC are right ventricular dominance, ventricular asymmetry, small posterior wall of LA, which is smooth, rounded, and hyper‐echogenic, absence of normal pulmonary venous flow, presence of a confluent vein, and prolongation of the distance between the left atrium and the descending aorta (Picture 2). The presence of a confluent vein (twig sign) posterior to the left atrium in TAPVC cases has been presented as one of the most important findings 1,2 . It has been shown that 80%–90% of pulmonary venous return anomalies occur in atrial septal defects of the superior vena cava sinus type 3 …”
Section: Picturementioning
confidence: 99%
“…The presence of a confluent vein (twig sign) posterior to the left atrium in TAPVC cases has been presented as one of the most important findings. 1,2 It has been shown that 80%-90% of pulmonary venous return anomalies occur in atrial septal defects of the superior vena cava sinus type. 3 In our case, all findings suggestive of TAPVC were found in the four-chamber section.…”
mentioning
confidence: 99%